Host and molecular mechanisms behind the persistence of equine strangles - McLinden, L.A. (2025)
Background: Equine strangles is a widespread and highly infectious disease caused by the bacterium Streptococcus equi subspecies equi (S. equi). Despite the long history of strangles, much is still unknown about S. equi and the disease it causes. Understanding the complex interplay between host and bacterial factors that contribute to the carrier state is crucial for effective management of equine strangles. The aims of this project were to 1) evaluate the effectiveness of a strangles screening protocol at a UK welfare centre equids and 2) use nanopore sequencing alongside bioinformatic analysis to investigate structural variants in acute and persistent S. equi isolates Methods: Phase 1: The clinical records of 626 equids admitted to a UK welfare centre between 2017 and 2021 were analysed. Admitted equids were subject to a strangles screening process consisting of paired dual target iELISA serological tests and guttural pouch endoscopy and lavage. Phase 2: The genomes of 11 acute and persistent S. equi isolates were analysed using nanopore sequencing technologies to investigate structural variants. Results: Phase 1: Retrospective analysis of the clinical records of admitted equids found that the most effective way to diagnose strangles was through guttural pouch endoscopy and lavage. No host factors or haematological parameters were significantly associated with strangles carriage. The dual target iELISA was found to be unreliable for the purpose of carrier detection. Phase 2: Deletions and inversions were found in key genomic regions including genes encoding the hyaluronic acid capsule and key sortase-processed cell surface proteins. A prophage was also found, integrated within genes encoding for the hyaluronic acid capsule.